Klasifikasi Genus Karang Keras (Scleractinia) dengan Metode Gray Level Co-Occurrence Matrix - Muh. Ihsan As Sauri; Agus Wahyu Widodo; Oktiyas Muzaky Luthfi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Coral reef ecosystems are very important for the source of life for a variety of marine biota. Coral reefs have ecological and economical benefits, so it is necessary to carry out regular monitoring so that the ecosystem is well maintained. This monitoring is carried out so that the handling of management runs properly, for this purpose coral identification activities are needed in a certain area. Identification of corals is not as easy as identifying plants, animals or other creatures that have common terminology and have been established. Corals that have similar types like the example in Genus are difficult to do. Therefore it is necessary to classify the Hard Coral Genus (Scleractinia) with the Gray Level Counseling Matrix (GLCM) method. The class used is the genus Acropora, Echinopora, Porites and Fungia. Processing is carried out using the image of the coral with this type of genus by GLCM preprocessing. The features used in the GLCM process are Contrast, Entropy, Energy, Homogenity and Correlation values. The classification used is Support Vector Machine (SVM) with the results obtained by the four Genus still difficult to identify with the results of accuracy of 25%.